Corporate social responsibility reporting quality, board characteristics and corporate social reputation. Issue 1 (2nd February 2015) - Lu, Yingjun; Abeysekera, Indra; Cortese, Corinne
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to examine the influence of corporate social responsibility (CSR) reporting quality and board characteristics on corporate social reputation of Chinese listed firms. Design/methodology/approach – Firms chosen for this study are drawn from a social responsibility ranking list of Chinese listed firms. The social responsibility rating scores identified by this ranking list are used to measure the social reputation of firms studied. The model-testing method is used to examine hypothesised relationships between CSR reporting quality, board characteristics and corporate social reputation. Findings – The results indicate that CSR reporting quality positively influences corporate social reputation but chief executive officer/chairman duality as a measure of board characteristics has a negative impact on corporate social reputation. Firm's financial performance and firm size also positively influence corporate social reputation. Research limitations/implications – The relatively small sample of firms for a cross-sectional study, and the proxies constructed for various concepts to empirically test hypotheses can limit generalising findings to firms outside the social responsibility ranking list. Future studies can undertake longitudinal analysis and compare socially responsible firms with others to expand empirical findings about corporate social reputation. Originality/value – This paper investigates the influences of CSR reporting quality and board characteristics on corporate social reputation in the context of a developing country, China.